2012
DOI: 10.1075/ijcl.17.2.05pre
|View full text |Cite
|
Sign up to set email alerts
|

The language of Islamic extremism

Abstract: Recent studies have sought to understand individuals' motivations for terrorism through terrorist material content. To date, these studies have not capitalised on automated language analysis techniques, partictilarly those of corpus linguistics. In this paper, we demonstrate how applying three corpus-linguistic techniques to extremist statements can provide insights into their ideology. Our data consisted of 250 statements (approximately 500,000 words) promoting terrorist violence. Using the online software to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…This was true both in the overall analysis of the concept frequencies across the three corpora and when we exposed the qualitative differences among the corpora. Compared to the U.K. officials’ counter‐messages, the Muslim authors’ counter‐messages showed (at both the word and concept level) similar use of religious terminology, similar use of stereotypical extremist language, and equivalent ways of using “contrastive” concepts (Prentice, Rayson, & Taylor, in press) when discussing religion, ethics, and language. These similarities give some evidence of a shared value system between Muslim extremist and counter‐extremist authors (Galtung, 1967).…”
Section: Discussionmentioning
confidence: 88%
“…This was true both in the overall analysis of the concept frequencies across the three corpora and when we exposed the qualitative differences among the corpora. Compared to the U.K. officials’ counter‐messages, the Muslim authors’ counter‐messages showed (at both the word and concept level) similar use of religious terminology, similar use of stereotypical extremist language, and equivalent ways of using “contrastive” concepts (Prentice, Rayson, & Taylor, in press) when discussing religion, ethics, and language. These similarities give some evidence of a shared value system between Muslim extremist and counter‐extremist authors (Galtung, 1967).…”
Section: Discussionmentioning
confidence: 88%
“…Some of the issues discussed so far have been addressed in corpus-assisted discourse studies, which incorporated corpus linguistics methodology and (semi)automated text analysis techniques (Baker, 2006;Baker et al, 2008;Krishnamurty, 1996;Prentice et al, 2012;Taylor, 2014). For example, Krishnamurty's (1996) study of the nearsynonyms ethnic, racial, and tribal demonstrated the value of combining qualitative analysis of small text samples with automated analysis of large corpora.…”
Section: Cda: Assumptions and Evolution Of Research Methodologymentioning
confidence: 97%
“…He analyses a corpus of messages sent to the Teenage Health Freak website through which young people can receive health advice. Prentice, Rayson and Taylor (2012) analyse features of the language of Islamic extremism. For this purpose they collected a corpus containing 250 extremist texts downloaded from the Internet.…”
Section: Corpora For the Analysis Of Discoursesmentioning
confidence: 99%